PELATIHAN PEMBUATAN AGAR-AGAR U TEUTOT REMPAH SEBAGAI SUPLEMEN DAYA TAHAN TUBUH PADA MASA COVID-19 - Allif Syahputra Bania; Nursamsu Nursamsu; Najihatul Faridy (Universitas Muhammadiyah Tapanuli Selatan, 2021)
U teutot is a typical drink passed down from generation to generation from the time of the Aceh sultanate. U (Coconut) as a basic material for PKM training is one of 17 plant species for Acehnese special food that comes from intensive cultivation. Perior's problems are the increasing need for immune supplements against the COVID-19 pandemic that is effective and has a selling value from ingredients that are easily obtained by PKK mothers in Gampong Bayeun, Birem Bayeun District, East Aceh Regency, especially coconut and spices and the lack of knowledge of PKK mothers in the use and process of entrepreneurship for immune supplements. Justification of Solutions to Partner Problems is training in making jelly from spice-roasted coconut as an immune supplement for PKK mothers in Bayeun Village during the COVID-19 outbreak and increasing the empowerment of mothers in the entrepreneurial process and making natural immune supplements in the form of jelly from spice-roasted coconut during the COVID-19 pandemic. Implementation methods are field survey, schedule determination, preparation, training, implementation, monitoring and evaluation.